Answer:
Option A
Step-by-step explanation:
Since the "y" variable is inside a root, we need to square both sides of the equation to open the root and solve for y.
<u>When squaring both sides, we get;</u>
![\implies \sqrt{2x + y - 3z} = 5](https://tex.z-dn.net/?f=%5Cimplies%20%5Csqrt%7B2x%20%2B%20y%20-%203z%7D%20%20%3D%205)
![\implies(\sqrt{2x + y - 3z})^{2} = 5^{2}](https://tex.z-dn.net/?f=%5Cimplies%28%5Csqrt%7B2x%20%2B%20y%20-%203z%7D%29%5E%7B2%7D%20%20%20%3D%205%5E%7B2%7D)
![\implies2x + y - 3z = 25](https://tex.z-dn.net/?f=%5Cimplies2x%20%2B%20y%20-%203z%20%20%3D%2025)
Now, simply isolate the y-variable to determine its value. This can be done by subtracting 2x on both sides of the equation.
![\implies2x + y - 3z = 25](https://tex.z-dn.net/?f=%5Cimplies2x%20%2B%20y%20-%203z%20%20%3D%2025)
![\implies2x + y - 3z - 2x = 25 - 2x](https://tex.z-dn.net/?f=%5Cimplies2x%20%2B%20y%20-%203z%20-%202x%20%3D%2025%20-%202x)
![\implies y - 3z = 25 - 2x](https://tex.z-dn.net/?f=%5Cimplies%20y%20-%203z%20%3D%2025%20-%202x)
Now, add 3z both sides of the equation to further isolate the y-variable.
![\implies y - 3z + 3z = 25 - 2x + 3z](https://tex.z-dn.net/?f=%5Cimplies%20y%20-%203z%20%2B%203z%20%3D%2025%20-%202x%20%2B%203z)
![\implies y = 25 - 2x + 3z](https://tex.z-dn.net/?f=%5Cimplies%20y%20%3D%2025%20-%202x%20%2B%203z)
Therefore, Option A is correct.